2016
DOI: 10.1080/00224545.2016.1184127
|View full text |Cite
|
Sign up to set email alerts
|

Disgusted but not afraid: Feelings toward same-sex kissing reveal subtle homonegativity

Abstract: Overt sexual prejudice is declining, but heterosexuals who report little to no prejudice may still harbor subtle biases against gay men and lesbians. We examined implicit prejudice in a sample of 37 heterosexual college students who reported little or no sexual prejudice, using the Affect Misattribution Procedure (AMP) and psychophysiological measures of affect. Skin conductance, heart rate, and facial electromyographic responses were recorded as participants viewed photos of mixed- and same-sex couples kissin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…Homophobia was associated with negativity in response to these displays of PDA amongst sexual minorities, which is in line with previous researchers' findings when examining attitudes toward displays of homosexual relationships and sex (Bernat et al, 2001;Kiebel et Parrott et al, 2006). When participants self-reported higher tolerance or acceptance toward sexual minorities, their results reflected higher tolerance as well.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Homophobia was associated with negativity in response to these displays of PDA amongst sexual minorities, which is in line with previous researchers' findings when examining attitudes toward displays of homosexual relationships and sex (Bernat et al, 2001;Kiebel et Parrott et al, 2006). When participants self-reported higher tolerance or acceptance toward sexual minorities, their results reflected higher tolerance as well.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have consistently found that men are more explicitly sexually prejudiced than women (Kiebel et al, 2017;Monto & Supinski, 2014). Viewing gay erotica is associated with negative affect, anger-hostility, and feelings of fear in men who have self-reported being sexually prejudiced (Bernat, Calhoun, Adams, & Zeichner, 2001;Parrott, Zeichner, Hoover 2006).…”
Section: Journal Ofmentioning
confidence: 93%
See 2 more Smart Citations
“…Despite the great strides made in achieving social inclusion, depathologization, and the consequent destigmatization of sexual minorities, rejection, discrimination, and prejudice indexes remain high. In addition, more subtle or implicit forms of discrimination have emerged (Lingiardi et al, 2015;Kiebel et al, 2017;Vial, 2019) that continue to threaten the everyday lives of LGBT people and result in high stress levels for them (Barrientos et al, 2014). The studies published by Meyer (1995Meyer ( , 2003 on the Minority Stress Model have made it possible to generate a large body of evidence on how permanent victimization, discrimination, and homolesbotrans negativity cause LGBT people to display poorer mental health indicators than their heterosexual and cisgender peers (APA/Division 44, 2000;Meyer, 2003;Logie, 2012;Hatzenbuehler et al, 2013;Barrientos et al, 2014;Bidell and Stepleman, 2017).…”
Section: Persistence and Emergence Of New Forms Of Discrimination Andmentioning
confidence: 99%